Long-acting reversible and permanent contraceptives utilization and its associated factors among married women who desire no more children in Ethiopia: A multilevel analysis - Nuhamin Tesfa Tsega; Wondimnew Mersha Biset; Getie Mihret Aragaw; Saron Abeje Abiy; Tilahun Nega Godana; Abera Dessie Dagnaw; Gashaw Awoke Haile; Daniel Gashaneh Belay; Berihun Agegn Mengistie (PLoS ONE, 2025)
Objective This study aimed to investigate long-acting reversible and permanent contraceptives (LARPCs) utilization and its associated factors among married women who desire no more children in Ethiopia. Methods Secondary datasets from the 2016 Ethiopian Demographic and Health Survey was used for the study. A total weighted sample of 3,756 married or in union reproductive age women who desire no more children were included in the analysis. Data was cleaned, weighted, and analyzed using STATA Version 14 software. A multi-level logistic regression analysis was conducted to consider the hierarchal nature of the demographic and health survey data. In a multivariable multilevel logistic regression model, an adjusted odds ratio (AOR) with a corresponding 95% confidence interval (CI) and p value <0.05 was used to declare the significant associated factors of LARPCs utilization. Results The overall utilization of LARPCs among married women who desire no more children was 12% [95%CI: 10.99, 13.07]. In the multivariable multilevel analysis; being female household heads [AOR = 0.60; 95%CI: 0.40, 0.92], husband primary level of education [AOR = 1.57; 95%CI: 1.18, 2.07], employed women [AO R = 1.34; 95%CI: 1.04, 1.74], women from middle wealth index [AOR = 1.45; 95%CI: 1.02, 2.07], women who visited health facility in the last 12 months [AOR = 0.69; 95%CI: 0.54, 0.88], women residing in small peripherals [AOR = 0.20, 95%CI: 0.05, 0.82], and women from communities with low poverty [AOR = 2.25, 95%CI: 1.26, 3.99] were significantly associated with LARPCs utilization. Conclusion In Ethiopia, LARPCs utilization among married women who desire no more children was very low. Both individual and community-level factors were significantly associated with LARPCs utilization. Thus, individual and community-level interventions that encourage husband education, maternal occupation, and giving special attention for women who live in small peripheral areas and female-headed households are better.